Buffalo Potency Development Strategy in Magelang - Rahardjo, Budi; Novitaningtyas, Ivo; Ikhwan, Khairul; Cahyani, Annisa Putri (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
Livestock contributes to fulfilling the protein needs of the Indonesian people, but meat self-sufficiency is still far from being expected in Indonesia. Substitute products are needed to accompany beef in order to achieve meat self-sufficiency in Indonesia. The potential of buffalo as livestock needs to be optimized to support the achievement of meat self-sufficiency in Indonesia. It takes a strategy in planning the development of a comprehensive, effective, and efficient buffalo farm. This study aims to determine the population of buffalo and other ruminants in Magelang Regency and to analyze the strategy of developing buffalo farming in Magelang Regency. The research used the descriptive qualitative method. Data were analyzed using Location Quotients (LQ) modeling and the Strength, Weakness, Opportunities, and Threats (SWOT) matrix. The results show that the areas that have the potential as locations for buffalo development in Magelang Regency based on the highest LQ index are Bandongan District, Secang District, Mungkid District, Dukun District, and Muntilan District. The results of the strategy analysis in an effort to develop the potential of buffalo in Magelang Regency through a SWOT analysis are in quadrant I.Keywords: strategy, buffalo livestock, location quotient, SWOT